What is The Effectiveness of Case Management on Health Outcomes for Elderly Patients with HIV/AIDS? : A Systematic Review - Yesi Winda Septriani Meliala; Deddy Zulkarnaen; A.Rafika Yunus (International Medical Journal Corp. Ltd, 2026)
Introduction: The aging of the HIV epidemic necessitates effective interventions for people living with HIV (PLWH) aged 50 years and older, who face unique challenges including multimorbidity, polypharmacy, and frailty. This systematic review evaluates the effectiveness of case management (CM) on health outcomes in elderly PLWH. Methods: A systematic search was conducted for studies evaluating CM interventions in PLWH aged ≥50 years. Outcomes included viral suppression, retention in care, medication adherence, comorbidity management, quality of life (QoL), and healthcare utilization. Results: Among 80 included studies, significant positive effects were observed. Nurse-led CM in Taiwan achieved 93.5% viral suppression and 73.6% retention vs. 31.7% in controls (p<0.001) [2,3]. The MARTAS intervention in Ukraine improved linkage to care (84.4% vs. 33.8%; aRR=2.45) [4]. In Medicare beneficiaries (≥65 years), medication therapy management increased ART adherence (aOR=1.15) and reduced opioid-benzodiazepine co-use [5]. The AIMS nurse-led strategy reduced treatment failure (7.3% vs. 16.8%) and was cost-saving [6]. Pharmacist-led interventions improved lipid profiles (18% to 4.9% high cholesterol, p<0.001) [14] and accelerated viral suppression (HR=1.37) [53]. Housing CM doubled viral suppression likelihood (aOR=2.1) [21]. For elderly-specific programs, the Golden Compass program improved self-rated health (p=0.015) [11] and comprehensive geriatric assessment (CGA) identified high rates of frailty (60%) and led to deprescribing in >50% [9,12]. Discussion: CM is highly effective for elderly PLWH when targeting specific barriers: linkage to care, adherence, comorbidity management, or housing. Pharmacist and nurse-led models show consistent positive outcomes. Most elderly-specific evidence is observational but promising. Conclusion: Case management significantly improves viral suppression, retention, adherence, and comorbidity control in elderly PLWH. Geriatric-focused CM should be integrated into HIV care for older adults.